Evaluating Digital Health Capability at Scale Using the Digital Health Indicator - Woods, Leanna; Eden, Rebekah; Pearce, Andrew; Wong, Yu Ching Ides; Jayan, Lakshmi; Green, Damian; McNeil, Keith; Sullivan, Clair (Applied Clinical Informatics, 2022)
Background Health service providers must understand their digital health capability if they are to drive digital transformation in a strategic and informed manner. Little is known about the assessment and benchmarking of digital maturity or capability at scale across an entire jurisdiction. The public health care system across the state of Queensland, Australia has an ambitious 10-year digital transformation strategy.Objective The aim of this research was to evaluate the digital health capability in Queensland to inform digital health strategy and investment.Methods The Healthcare Information and Management Systems Society Digital Health Indicator (DHI) was used via a cross-sectional survey design to assess four core dimensions of digital health transformation: governance and workforce; interoperability; person-enabled health; and predictive analytics across an entire jurisdiction simultaneously. The DHI questionnaire was completed by each health care system (n = 16) within Queensland in February to July 2021. DHI is scored 0 to 400 and dimension score is 0 to 100.Results The results reveal a variation in DHI scores reflecting the diverse stages of health care digitization across the state. The average DHI score across sites was 143 (range 78–193; SD35.3) which is similar to other systems in the Oceania region and global public systems but below the global private average. Governance and workforce was on average the highest scoring dimension (x̅= 54), followed by interoperability (x̅ = 46), person-enabled health (x̅ = 36), and predictive analytics (x̅ = 30).Conclusion The findings were incorporated into the new digital health strategy for the jurisdiction. As one of the largest single simultaneous assessments of digital health capability globally, the findings and lessons learnt offer insights for policy makers and organizational managers.
Keywords: digital health; digital capability; digital maturity; digital hospitals; digital transformation; health information management; organizational characteristics